Fourier transform infrared (FTIR) spectroscopy as a tool to characterize exercise and physical activity: a systematic review - Valente, P. A.; Mota, S. I.; Teixeira, A.; Ferreiro, E.; Sarmento, H.; Cipriano, I.; Campos, J. R.; Rama, L.; Oliveira, P. J. (Sports Medicine, 2025)
Background: Over the past few decades, the scientific community has recognized the impact of physical activity on health and performance. In parallel, researchers have been actively exploring novel methodologies to analyze the physiological and metabolic responses to exercise. Fourier transform infrared spectroscopy has emerged as a powerful tool in this effort, offering the potential to provide unique insights into exercise-related changes at the molecular level. Objective: The primary goal of this systematic review is to confirm the viability of utilizing Fourier transform infrared spectroscopy for the analysis of the biochemical changes associated with physical exercise and its potential applications. Methods: This systematic review adhered to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and examined studies employing Fourier transform infrared spectroscopy to analyze exercise and physical activity, focusing on a biological sample collection and spectral analysis. Four databases (PubMed, SPORTDiscus, Web of Science, and Scopus) were searched, and inclusion criteria encompassed original English-language studies involving human participants aged 18-50 years, a biological sample collection (urine, saliva, and blood), and the use of Fourier transform infrared spectroscopy. The studies were analyzed considering the type of exercise or sport that was investigated, and also the type of spectral analysis conducted. Results: The review encompassed 15 studies that demonstrated the versatility of Fourier transform infrared spectroscopy in assessing various aspects of exercise, including metabolism, cardiovascular responses, and muscular fatigue. The largest study evaluated 57 athletes from several different sports. On average, almost all the studies were performed with around 20 athletes. Notably, the technique`s holistic approach allows for a comprehensive analysis of the complex network of metabolites and proteins within the human body. Data analysis methodologies, particularly when coupled with machine learning, show great potential for advancing the field of sports science. Conclusions: Fourier transform infrared spectroscopy emerges as a promising tool for monitoring and enhancing the performance of high-level athletes, preventing overtraining or even over-reaching, and assessing metabolism. Its accuracy, efficiency, and affordability also make it a candidate for broader applications in assessing the health and fitness of the general population. Future research should explore its applicability across diverse exercise modalities and demographic groups, aiming to prescribe exercise plans that consider a multitude of parameters for larger, more intricate exercise cohorts.